Modelling Seasonally Integrated Processes and Processes with Seasonal Volatility for Daily Data - Kufel, Tadeusz (Modelowanie procesów sezonowo zintegrowanych oraz o sezonowej zmienności dla danych dziennych, 2010)
Cyclical, high frequency economic processes contain complicated internal structure with possible time-varying average and variance and cyclical varying average and variance. We can ask the following questions: Have high frequency economic processes got deterministic or stochastic cyelicity? Can cyclical variability in high frequency economic processes be described by GARCH model with deterministic cyelicity? The paper contains discussion of the issues of testing seasonal unit root by new stationary test for high frequency processes proposed by D.A. Dickey in 2009. All discussed problems will be illustrated by examples for daily data with analysis of heteroscedasticity by GARCH (q, p) model.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 91, s. 84-94
Keywords: high frequency economic data; testing seasonal unit root for high frequency processes; GARCH models